OPPORTUNITIES AND VERSATILITY OF ONLINE LEARNING IN HIGHER EDUCATION INSTITUTIONS - Diasamidze Mzia; Shotadze Anna; Gvinjilia Tsira (International Journal of Innovative Technologies in Social Science, 2022)
The article discusses the solution of learning problems based on statistical studies of transformed learning methods due to the Covid - 19 World Pandemic. Everyone knows that the entire "educational world" (and not only) has switched to the distance learning method. For this, various electronic platforms were used: faсebook, skype, google, other social networks, Zoom, TIMS, etc. Teaching methods, the form and assessment criteria, student activity, their feedback, a different approach to the intensity of student attendance have changed. It is no secret to anyone that the form of education used is still a way out of the current situation, and not the goal of teaching. More than two years have passed, and with confidence you can evaluate the process, draw conclusions, share experience. The importance of distance learning is confirmed by some changes in the legislative part of the States. The Law of Georgia on Higher Education has a whole chapter 474 - "e-learning" and chapter 477 - "distance learning" [1]. Based on the assessment of the statistical information studied by us, conclusions and recommendations for the use of "online learning" as one of the methods are given. Along with the strengths, there are also weaknesses, the overcoming of which would make the educational process more attractive and focused on the quality of the learning outcome.